An NHC–phosphinidenyl as a synthon for new group 13/15 compounds. Issue 54 (22nd June 2017) - Lemp, Otfried; Balmer, Markus; Reiter, Kevin; Weigend, Florian; von Hänisch, Carsten
Abstract : The deprotonated parent phosphinidene SIMesPK (SIMes = 1, 3-bis(2, 4, 6-trimethylphenyl)imidazolin-2-ylidene) was used as a synthon for new group 13/15 cycles and cage compounds such as [SIMesPGatBu2 ]2 . Abstract : The parent phosphinidene SIMesPH (1 ) (SIMes = 1, 3-bis(2, 4, 6-trimethylphenyl)imidazolin-2-ylidene) was treated with benzyl potassium to form the metalated species SIMesPK (2 ), which was used as a synthon for the new group 13/15 cycles and cage compounds [SIMesPGa t Bu2 ]2 (3 ), [SIMesP(Ga t Bu2 )2 Cl] (4 ) and [K(SIMesP)3 Al t Bu] (5 ).